ANALISIS HUKUM TERHADAP PUTUSAN PN MEDAN NOMOR 637/PDT.G/2017/PN.MDN TENTANG WANPRESTASI DALAM PERJANJIAN UTANG PIUTANG - Darmawan, Said Hendri (LPPM Universitas Bina Bangsa, 2025)
The study reveals the complexity of legal issues related to debt agreements, especially in the context of proving and assessing elements of default. An in-depth study of this court settlement provides a significant contribution to understanding the application of the principles of contract law and the interpretation of judges in resolving contractual settlements. As well as the importance of clarity of agreement clauses, good faith for the parties, and proportional settlement mechanisms in debtor-debtor legal relations. Recommendations submitted include the need to develop more comprehensive legal interpretation guidelines in assessing defaults.